Kajian Tentang Madrasah - Muhammad Ridwan Efendi; Wedra Aprison (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2024)
This study aims to investigate various aspects related to madrasas, Islamic educational institutions that have an important role in educating generations of Muslims. This research involves literature analysis and empirical studies to understand the history, curriculum, teaching methods, and social and cultural impact of madrasas in society. Historical research involves analysis of the development of madrasas from the past to the contemporary era, while analysis of curriculum and teaching methods includes evaluation of the educational approaches used in madrasas. In the context of social and cultural impacts, this study tries to explore the contribution of madrasas to religious identity, social values and community integration. It is hoped that the results of this study will provide deeper insight into the role and significance of madrasas in the context of Islamic education and their contribution to the social and cultural development of society. The implications of these findings can be the basis for further improvement and development of the madrasa education system to meet the demands of the times and the need for quality education.